Variation in soil nutrient levels under multispecies hedgerow cropping with plantain - Owoeye, L.G.; Ortíz, R.; Gichuru, M.P.; Vuylsteke, D.R. (International Society for Horticultural Science, 2000)
Spatial nutrient distribution was studied under a multi-species hedgerow cropping with plantain on an acid ultisol in southeastern Nigeria. The objective of this study was to evaluate variation in soil nutrients under alleys formed by multi-species hedgerows at three sampling sites: 0.5 m around plantain stands, from 0.5 m to 1.5 m away from plantain stands and under multi-species hedgerows. Nutrient distribution (0-10 cm soil layer) varied significantly across the three sampling sites. This study showed that readily available mulch materials from multi-species hedgerow can enhance soil nutrient recycling and organic residues along the cropping alley. The integration of cultural practices as an alternative to bush fallow systems could sustain the production of plantain in the humid tropic zone of Africa.